Characteristics Of Chronic Kidney Failure Patients Using Vascular Access for Hemodialysis in Vascular Surgical Division Dr. Mohammad Hoesin General Hospital Period 1 Januari – 31 Desember 2018 - Kemas Muhammad Dahlan; Wahyu Sholekhuddin; Fahmi Jaka Yusuf (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Background: Hemodialysis has been accepted as a method of treatment in patients with CKD in stage 5. A-V fistula is the closest ideal hemodialysis vascular access, so that it can reduce morbidity and mortality of CKD patients. Methods: is a retrospective descriptive study with data obtained from the A-V fistula surgery form archive in the Vascular and Endovascular Division of the Department of Surgery, FK UNSRI in January 2018-December 2018 and from the patient's medical record. Data processing was carried out with SPSS 16.0. Results: of the study obtained 203 patient data with the use of AV Shunt that met the inclusion criteria. The mean age of patients was 50.53 years. There were 114 (56%) male patients and 89 (44%) female patients. Risk factors such as smoking were found in 9 (4%) patients. History of the disease prior to experiencing chronic renal failure was hypertension in 115 patients (56.6%) and diabetes in 81 (40%). There were 69 patient’s Hb data before AV shunt with Hb <7 (1%) in 2 people, 7-8.9 (33%) 67 people, 9-10.9 (53%) 108 people, > 11 (13%) 26 people. 128 (63%) patients had double lumen catheters installed in the right jugular, 5 (2%) patients were placed in the left jugular, and 70 (34%) patients did not have a double lumen catheter. Conclusion: A total of 169 (83%) patients had a history of using AV Shunt. There were 71 (35%) patients with the wrist region anastomosis, 132 (65%) patients with cubiti region anastomosis. Native AV shunt was the most commonly performed in 202 (99.5%) patients. There were no recorded complications after AV Shunt placement in 99 (48.8%) patients, 51 (25.2%) patients had AVF branches, 23 (11.3%) had AV Shunt rupture, 18 (8.8%) AVF stenosis, 1 (0.5%) central stenosis, 1 (0.5%) thrombus, and 11 (5.4%) infections. A total of 167 (82.2%) patients took AV Shunt after 3 months.